The impact of eight weeks of resistance training on some angiogenesis indicators in women with breast cancer - Fazlollah Fathollahi Shourabeh; Bahman Tarverdizadeh; Mozhgan Keihani (Mashhad University of Medical Sciences, 2017)
Introduction: Breast cancer is the most prevalent cancer in women. In Iran, %16 of all cancers in both male and female is related to breast cancer, and it has the first rank among Iranian women. Increasing levels of angiogenesis factors including NO, FGF, and VEGF is threatening in first stages of cancer, but it helps treatment and recovery in therapeutic level. Therefore this study was performed with aim to evaluate the impact of eight weeks of resistance training on some angiogenesis indicators in women with breast cancer. Methods: This semi-experimental study was performed on 30 women with breast cancer who had undergone therapeutic level. They were randomly divided into two groups, control group (n=14) and resistance training group (n=16). The experimental group performed resistance training for 8 weeks, per week three sessions, with the intensity of 50-70 percent of 1RM. To study the variables of NO, FGF, and VEGF, 48 hours before and after the last session of training, the blood samples were taken of participants. Data were analyzed by SPSS software (version 19) and independent and dependent T test. P<0.05 was considered significant. Results: The eight weeks of resistance training significantly increased the levels of VEGF, FGF and NO in experimental group than control group (P=0.0001). Conclusion: The eight weeks of resistance training increased the level of some angiogenesis indicators and this increase in angiogenesis indicators leads to increased muscle mass and reduced fatigue in patients with breast cancer.